Urgensi digital marketing dan sosial media untuk pengembangan UMKM - Nur, Mujtaba Alfan (Maliki Interdisciplinary Journal, 2023)
Increasing globalization and developments in information technology have provided a new foundation for marketing micro, small and medium enterprises (MSMEs). However, in the context of implementing digitalization, a number of obstacles arise. The main challenges include limited access to technology, limited knowledge of MSME owners regarding digital marketing strategies, and concerns about competitors. The purpose of writing this article is to overcome these obstacles by offering a solution in the form of optimizing social media as an effective tool in implementing digital marketing strategies. Through a targeted approach and leveraging various social media platform features, MSMEs can build a strong digital presence, increase customer engagement and expand market reach. The research method used is a combination of literature study methods and field observations.